The outcomes of flavectomy with foraminotomy versus hemilaminectomy with foraminotomy in patients with lumbar neurogenic intermittent claudication: A comparative study in Sulaimaniyah, Kurdistan region, Iraq - Abdalla, Rawsht Omed; Barawi, Omar Ali Rafiq; Mahmood, Hamid Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: The main prominent and classical symptom of lumbar spinal stenosis is intermittent neurogenic claudication, which is characterized by pain, aching, cramping, and paresthesia in the lower extremities induced by standing, walking, and back extension. Surgical decompression is the best choice when conservative methods fail. There are various decompressive techniques have been introduced, among them flavectomy with foraminotomy (F/F) and hemilaminectomy with foraminotomy (H/F). Objectives: To compare the outcomes of F/F versus H/F, in patients with neurogenic claudication and to determine the predictors that may interfere with the outcomes. Materials and methods: Twenty-one patients with lumbar spinal stenosis having neurogenic claudication were divided into two groups sequentially. The first group (n=10) underwent F/F, and the other group (n=11) underwent H/F. Follow-up was done in the first and sixth months postoperatively for postoperative complications, Oswestry disability index (ODI), claudication distance, and patients' satisfaction regarding symptoms. Results: In the last follow-up, the first group, after F/F, showed improvement in walking distance as 80% reported unlimited,10% improved with >1500 m, and 10% less improved with 500 m. These cases got lesser ODI scores and mostly were <10% despite one case remaining with moderate disability. Patient satisfaction rates were higher but not significant. While those who underwent H/F, nearly 40% showed unlimited walking distance, 45% improved with >1000 m, the remaining reported less improvement, and one remained with <100 m walking distance. Their ODI scores were higher than the previous group, mostly >10%, and 2 cases remained with moderate disability and complained of remaining back ache and leg paresthesia while improving in walking distance. Conclusions: both surgical procedures showed benefits in treating lumbar spinal stenosis, but F/F is better than H/F due to its high success and patient satisfaction rate. It can significantly improve a patient's quality of life by increasing postoperative walking distance, resolving neurogenic claudication, reducing ODI score, and relieving back pain, lower limbs pain, and paresthesia postoperatively. The increase in age is associated with less improvement after both procedures.
Keywords: Lumbar spine stenosis; intermittent neurogenic claudication; flavectomy; foraminotomy; hemilaminectomy